Origins of Combination Therapy for Tuberculosis: Lessons for Future Antimicrobial Development and Application - Christopher A. Kerantzas (American Society for Microbiology, 2017)
ABSTRACT Tuberculosis is a global health problem that causes the death of approximately 1.5 million people worldwide each year (WHO, p. 1–126, Global Tuberculosis Report, 2015). Treatment of drug-susceptible tuberculosis requires combination antimicrobial therapy with a minimum of four antimicrobial agents applied over the course of 6 months. The first instance of combination antimicrobial therapy applied to tuberculosis was the joint use of streptomycin and para-aminosalicylic acid as documented by the Medical Research Council of the United Kingdom in 1950. These antimicrobial drugs were the product of many decades of investigation into both organism-derived antibiotics and synthetic chemotherapy and were the first agents in those respective categories to show substantial clinical efficacy and widespread use for tuberculosis. The events leading to the discovery and application of these two agents demonstrate that investments in all aspects of research, from basic science to clinical application, are necessary for the continued success of science in finding treatments for human disease. This observation is especially worth considering given the expanded role that combination therapy may play in combating the current rise in resistance to antimicrobial drugs.